Non-surgical treatment of gastric emphysema with intraabdominal free gas and hepatic portal venous gas: Lessons from a rare case. (July 2020) - Furihata, Tadashi; Ushiku, Takafumi; Murayama, Isao; Sato, Jun; Kamo, Tomohisa; Naoe, Fumiyo; Hasegawa, Tetsuo; Watanabe, Yoshihiro; Kasakura, Yuichi; Furihata, Makoto
We herein describe a case of an 83-year-old man who presented with epigastralgia, vomiting, and abdominal distention. The physical abdominal examination revealed mild tenderness. Computed tomography revealed intramural gastric gas spread throughout the stomach, intraabdominal free gas, and hepatic portal venous gas. We diagnosed gastric emphysema with intraabdominal free gas and hepatic portal venous gas. We selected a wait-and-watch approach because physical examination did not show any peritoneal signs, although the radiological examinations showed remarkable findings. As a result, he received conservative therapy with fasting, intravenous infusion of antibiotics, and gastric decompression by nasogastric intubation. The patient was relieved of the symptoms, and follow-up computed tomography showed that all the abnormal gas disappeared soon after the treatment. In conclusion, the intramural gastric gas even with both intraabdominal free gas and hepatic portal venous gas does not always require surgical intervention. In case clinicians including general surgeons and physicians encounter intraabdominal free gas with hepatic portal venous gas, gastric emphysema should be considered in the different diagnosis. Lack of knowledge may lead to misdiagnosis, which may result in unnecessary surgical intervention.